Multibody Dynamics 2019 : Proceedings of the 9th ECCOMAS Thematic Conference on Multibody Dynamics /: Proceedings of the 9th ECCOMAS Thematic Conference on Multibody Dynamics. ([2020]) - Unknown
No abstract available